Study of B-s(0)-(B-s(0))over-bar oscillations and B-s(0) lifetimes using hadronic decays of B-s(0) mesons - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (2000)
Oscillations of B0s mesons have been studied in samples selected from about 3.5 million hadronic Z decays detected by DELPHI between 1992 and 1995. One analysis uses events in the exclusive decay channels: B0s → D-sπ+ or D-sa+1 and B0s → D̄0K-π+ or D̄0K-a+1, where the D decays are completely reconstructed. In addition. B0s-B0s̄ oscillations have been studied in events with an exclusively reconstructed Ds accompanied in the same hemisphere by a high momentum hadron of opposite charge. Combining the two analyses, a limit on the mass difference between the physical B0s states has been obtained: ΔmB0s > 4.0 ps-1 at the 95% C.L. with a sensitivity of ΔmB0s = 3.2 ps-1. Using the latter sample of events, the B0s lifetime has been measured and an upper limit on the decay width difference between the two physical B0s states has been obtained: τB0s = 1.53+0.16-0.15(stat.) ± 0.07(syst.) ps ΔΓB0s/ΓB0s < 0.69 at the 95% C.L. The combination of these results with those obtained using D±sℓ∓ sample gives: ΔmB0s > 4.9 ps-1 at the 95% C.L. with a sensitivity of ΔmB0s = 8.7 ps-1. τB0s = 1.46 ± 0.11 ps and ΔΓB0s/ΓB0s < 0.45 at the 95% C.L.